Nutritional Status and Body Composition Based on Junk Food Consumption, Stress, and Sleep Quality among University Administrative Staff - Desiani Rizki Purwaningtyas; Anna Ahmiyanasari; Luthfiana Nurkusuma Ningtyas (Fakultas Kedokteran Universitas Sultan Ageng Tirtayasa, 2025)
Obesity remains a major nutritional issue among individuals of productive age. Dietary factors, including the consumption of junk food, along with lifestyle aspects such as stress levels and sleep quality, may serve as reinforcing risk factors for obesity, particularly among workers with low levels of physical activity, both in terms of nutritional status and body composition measurements. This study analyses the relationship between junk food consumption, stress levels, and sleep quality with nutritional status and body composition among university administrative staff. This research employed a quantitative approach using a cross-sectional study design. The study population consisted of 98 administrative staff from a university in Jakarta, selected through simple random sampling. A microtoise and Bioelectrical Impedance Analysis (BIA) assessed nutritional status and body composition. Junk food consumption was measured through interviews using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), stress levels were assessed using the Depression Anxiety Stress Scale-42 (DASS-42), and sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). Data were analysed using univariate and bivariate methods, with Chi-square tests applied. The results showed that most of subjects (68.4%) were obese. There were significant associations between stress levels and sleep quality with nutritional status, body fat percentage, and visceral fat (P<0.05), although no significant relationship was found with muscle mass percentage. Poor sleep quality and high stress levels emerged as risk factors for obesity, as indicated by BMI, body fat percentage, and visceral fat.